The Implementation of Vocabulary Trees to Enhance Students’ Vocabulary Achievement - Yustih Yasin; Hasmirawati Injar La Sitiha (Seltics Journal: Scope of English Language Teaching Literature and Linguistics, 2021)
The purpose of this study was to determine the extent of the effect of the vocabulary trees technique on students' vocabulary achievement at SMAN 1 Wongeduku, SMAN 1 Wawotobi, and SMKN 1 Unaaha. This research is a qualitative research with a quasi-experimental design. Pre-test and post-test are used in order to determine the use of vocabulary trees in senior and vocational high school. The researcher found that the vocabulary trees technique improved students’ vocabulary achievement and made students active and creative in learning. It was proved when they were playing vocabulary trees most of them were active, thus because during playing vocabulary trees technique activities, they can know new vocabularies, and recognize most vocabularies correctly by using vocabulary trees technique in each school. It can be seen in real dates are; 1) , 2) , 3) the students’ achievement that students who are treated by vocabulary trees improved.